KARLEN V. GRIGORIAN (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
We will always remember Karlen V. Grigorian as a citizen, famous scientist and distinguished teacher. The bright memories of him will always remain in our hearts.